Efficient, Self‐Terminating Isolation of Cellulose Nanocrystals through Periodate Oxidation in Pickering Emulsions. Issue 20 (13th September 2018) - Liu, Peiwen; Pang, Bo; Tian, Lin; Schäfer, Timmy; Gutmann, Torsten; Liu, Huan; Volkert, Cynthia A.; Buntkowsky, Gerd; Zhang, Kai
Abstract: Many efforts have been made to isolate native nanocrystals from raw materials in the last two decades, such as cellulose nanocrystals (CNCs), but existing methods still suffer from low yields, complicated synthesis processes, and nonuniform sizes of obtained CNCs. This study concerns a facile, self‐terminating, and efficient method for the formation of uniform CNCs in high yields during the periodate oxidation process within Pickering emulsions. A biphasic system containing hexane with dissolved hexylamine and an aqueous solution of sodium periodate (NaIO4 ) was used as the reaction medium. Regulated by hexylamine, owing to its limited solubility in water, the pH value of the aqueous phase was enhanced to around 9.8, leading to the precipitation of sodium orthoperiodate (Na2 H3 IO6 ) nanoplates and thus the formation of the initial Pickering emulsions. During the gradual formation of cellulose nanofibers and then CNCs, CNCs were attracted to stabilize the interface of the Pickering emulsions, which prevented further decomposition of CNCs by the oxidizing agent in aqueous suspensions. Thus, this isolation strategy secured the efficient separation of CNCs based on their own particular amphiphilic properties and achieved a high yield of up to 56 wt %. Abstract : Take your Pickering : A facile, self‐terminating, and efficient method for the formation of uniform cellulose nanocrystals (CNCs) in high yields during the periodate oxidation process within Pickering emulsions. The precipitation of sodium orthoperiodate nanoplates leads to formation of Pickering emulsions. During the gradual formation of CNCs, they are attracted to stabilize the interface of the Pickering emulsions.